Teni zabytykh predkov . Shadows of Forgotten Ancestors - Paradzhanov, Sergei (Soviet Union, 1964)
The film is set among the Hutsul people of the Western Ukraine, an isolated ethnic group who live in the upper reaches of the mountain range. Their lives unfold within a harsh environment and an ornate cultural system little changed since the 18th century. The film opens with the deaths of Ivanko's brother, Olexa, crushed by a tree, and father, Pyotr Pavlichuk, killed outside the church by his rich neighbor Guteniuk. During the funeral procession for his father, Ivanko meets Guteniuk's daughter, Marichka, and the stage is set for the star-crossed lovers. Structured episodically, the film returns to Ivanko and Marichka as they fall in love and grow towards adulthood. Finally of an age to marry, Ivanko finds himself unable to do so, having been reduced to poverty by his father's death. Forced to work as a hired hand, he must leave his village and his beloved Marichka. Tragedy ensues and the remainder of the film concerns Ivanko's private and subtle dissolution as a result of this tragedy.